A new explicit formula for the Bernoulli and Genocchi numbers in terms of the Stirling numbers - Guo, Bai-Ni; Qi, Feng (Global Journal of Mathematical Analysis, 2015)
In the paper, the authors concisely review some explicit formulas and establish a new explicit formula for the Bernoulli and Genocchi numbers in terms of theStirlingnumbers of the second kind.